Breaking Barriers: Women Leading Schools in Chipinge District, Zimbabwe - Dube Albert; Edward Lambert; Kanbiro Orkaido Deyganto, (Journal of Women Entrepreneurship & Business Management (e-ISSN: 2583-8210), 2025)
This study investigated the administrative performance of female School Heads in both primary and secondary institutions across the Chipinge District of Zimbabwe. Recognizing the growing importance of gender equity in educational leadership, the research sought to understand how female School Heads navigate their roles and responsibilities within a traditionally male-dominated profession. A descriptive survey design was employed to systematically capture and analyze the experiences and effectiveness of these leaders. The research focused on a sample of 7 female School Heads selected from a total population of 41 School Heads. Data collection instruments included questionnaires and interview guides, complemented by document analysis. From each of the seven selected schools, five male and five female teachers were purposively sampled using homogeneous sampling techniques. Additional data were gathered from institutional records such as pass rate trends, school policies and circulars, school vision statements, departmental files, master timetables, and syllabi. Quantitative data were analyzed using tally marks and frequency counts, which were then converted into percentages. The pass rates percentages in female headed schools were quantitatively higher than those of their counter parts. Qualitative data from interviews and documentation were thematically analyzed to extract key insights. The findings indicated that female School Heads performed well across all six assessed administrative tasks. Based on these results, the study recommends that the Ministry of Primary and Secondary Education in Zimbabwe implement structured training programs focused on financial management for female school leaders. Additionally, the government should address teacher shortages to improve the teacher-pupil ratio and enhance educational quality. Finally, female School Heads are encouraged to collaborate with stakeholders in developing a shared school vision to foster collective ownership and alignment.